Design and analysis of car chassis - Mohamad Sazuan, Sarifudin (2012)
This project concerns on the assessment on making an analysis of the car chassis will fit all aspects and concepts according to the rules of Eco Marathon Challenge. The objective of this project to design and analyse of car chassis. To avoid any possibilities of failure of the structure and thus to provide enough supporting member to make the region stronger in term of deformation. Finite element analysis enables to predict the region that tends to fail due to loading. Besides that, need to utilize the feature of CAE software named as FEMPRO to get the distribution of stress and strain on the chassis, both component as well as the material costing. The main objective is to study the effect of load that applied in term of driver weight, the car body and the equipment.